Directive Speech Acts in Parenting and Politeness Implications Based on the Schools’ Missions: A Study on Kindergarten Teachers in Teaching Learning Process in Yogyakarta - Surono Surono; Sumarlam Sumarlam; Tri Wiratno; Sri Marmanto (Langkawi: Journal of The Association for Arabic and English, 2021)
This study aims to explore the types of directive speech acts (DSA) in parenting employed by the kindergarten teachers in the teaching-learning process in Yogyakarta, reveal their DSA patterns implying politeness, and determine the factors influencing the phenomena based on the schools' missions. Seven kindergartens and 10 teachers were recruited as the sample to participate in this research. The data were collected by interviewing the kindergarten teachers and observing and video recording their teaching-learning processes. Then, the data were analyzed by using the thematic coding method. Kreidler's (1998) theory was used to classify the DSA. The research findings showed that there were three main DSA realized by the kindergarten teachers in Yogyakarta, namely, command (f=543/45.10%), request (f=525/43.60%), and suggestion (f=136/11.30%). Concerning the three main DSA patterns based on the schools' missions, the Islamic and public-private kindergartens showed request, command, and suggestion respectively; meanwhile, the Christian and state kindergartens showed command, request, and suggestion respectively. It means the former showed more polite DSA and the latter showed less polite DSA. The factors influencing such phenomena were the institutional missions, teachers' teaching in one class, the teachers' teaching creativities, and cultural aspects. This study implies that language aspects, particularly DSA, need to be incorporated in parenting either in schools or home environments.